ChemInform Abstract: Traceless Directing Groups in Radical Cascades: From Oligoalkynes to Fused Helicenes Without Tethered Initiators. Issue 27 (18th June 2015) - Pati, Kamalkishore; dos Passos Gomes, Gabriel; Harris, Trevor; Hughes, Audrey; Phan, Hoa; Banerjee, Tanmay; Hanson, Kenneth; Alabugin, Igor V.
Abstract Diynes of type (I) and (III) containing methoxy groups as traceless directing groups undergo radical‐initiated cascades to form fused naphthalenes.